2017
DOI: 10.1177/0731684416689726
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of pretwisted delaminated composite stiffened shallow shells: A finite element approach

Abstract: This paper presents the effect of stiffeners on the free vibration response of delaminated composite shallow cylindrical shells employing the finite element method. An eight-noded isoparametric shell element based on the first-order shear deformation theory is combined with a three-noded isoparametric curved beam element in the present formulation. The stiffeners follow the nodal lines of the shell wherein the stiffness and mass of the stiffeners are lumped at the corresponding nodal points of the shell elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Their identical geometric parameters are: R s = 2m and L s = 5m. The material of the laminated shell is graphite-fiber-stiffened resin, with a laying angle of [0°/90°] [ 23 , 24 ]. In stiffened cylindrical shell, the number of curved beam is one, located at L s /2, and the material used is steel.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Their identical geometric parameters are: R s = 2m and L s = 5m. The material of the laminated shell is graphite-fiber-stiffened resin, with a laying angle of [0°/90°] [ 23 , 24 ]. In stiffened cylindrical shell, the number of curved beam is one, located at L s /2, and the material used is steel.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The above equation (37) is solved iteratively to find the natural frequency of the system. 3235 It is observed that after three iterations the result converges. The natural frequencies (ωn) are computed by using standard Eigen value solver algorithm.…”
Section: Hybrid Cnt Nanocompositementioning
confidence: 90%
“…While, using three dimensional modelling of composite blades, the free vibration study was reported by McGee and Chu 31 considering centrifugal effect of the blade. Rout et al also did several investigations on the free vibration of different rotating structures; such as composite stiffened shallow shells considering delamination, 32 pretwisted stiffened cylindrical shell 33 and stiffened plate. 34 Recently, Maji et al 35 conducted the free vibration analysis of rotating functionally graded carbon nanotube reinforced composite conical shell under varying thermal loading conditions employing finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…al. [39] carried out finite element analysis using first order shear deformation theory for the composite delaminated shallow cylindrical shells.…”
Section: Finite Element Methodsmentioning
confidence: 99%